Strategies for Internalizing Islamic Education Values through Nonformal Learning to Support the Achievement of Sustainable Development Goals (SDGs) - Reza Cahya Alfandi; Nurul Latifatul Inayati (Universitas Muhammadiyah Surakarta, 2024)
Objective: Education plays a pivotal role in developing human potential and internalizing moral values, particularly through non-formal institutions like the Al-Qur'an Education Park (TPQ). This study aims to analyze the challenges and strategies in internalizing Islamic educational values at TPQ Ar-Ridho Mosque, focusing on the methods employed and obstacles encountered. Utilizing a qualitative approach, data were collected through observation, interviews, and documentation. Theoretical framework: The theoretical framework draws on principles of Islamic education and its relevance to sustainable development goals (SDGs), emphasizing character-building aligned with Qur'anic teachings. Literature Review: A comprehensive literature review highlights the significance of TPQ in shaping students' moral character and the necessity of structured curricula to ensure effective learning. Methods: This research employs a qualitative approach to explore the internalization of Islamic education values at TPQ Ar-Ridho Mosque. Data were gathered through observation, in-depth interviews with educators and parents, and analysis of institutional documentation. Results: The findings reveal that TPQ Ar-Ridho plays a crucial role in character formation by implementing a structured curriculum grounded in Qur'anic values. However, challenges such as limited family involvement and inadequate infrastructure impede optimal educational outcomes. The study identifies that overcoming these challenges requires developing a curriculum tailored to Qur'anic educational standards and fostering active parental engagement. Collaboration among administrators, teachers, students, and parents, combined with regular evaluations, is essential to enhance the quality of education. These efforts align with the SDGs, particularly in promoting inclusive and equitable quality education. Implications: The implications of this research underscore the necessity of strengthening non-formal education systems to ensure moral and character development in young learners. It advocates for policies and practices that support TPQ's infrastructure and family participation, ensuring these institutions serve as effective agents of moral education. Novelty: The novelty of this study lies in integrating the concept of Qur'anic education with SDG principles to propose a sustainable model for TPQ development.